Narrative Policy Framework: Presidential Threshold Policy Toward the 2024 Election - Istiqoh, Akhdiva Elfi; Qodir, Zuly; Ahmad, Zakly Hanafi (Jurnal Bina Praja, 2022)
General elections are interpreted as a concrete manifestation of the implementation of democracy in Indonesia. However, the use of the Presidential Threshold is a matter of debate ahead of the 2024 General Election. The issue related to the Presidential Threshold has become a hot issue reported by the Indonesian media. The media have an essential role in shaping public narratives related to policymaking. The part of public records can create collective awareness by providing information about actors' choices in making a policy decision. This study aims to analyze how policymaking actors in Indonesia make decisions regarding using the Presidential Threshold in the 2024 General Election seen from the public narrative formed in the media. A Narrative Policy Framework (NPF) study will be conducted to describe and explain the structure of political narratives in policymaking. This study uses a qualitative research method with a QDAS (Qualitative Data Analysis Software) approach. The data sources in this study came from reputable online media in Indonesia. Research findings show that the government's attitude toward the House of People's Representatives (DPR) as policymakers does not waver towards implementing the 20% Presidential Threshold in the upcoming 2024 elections. However, the narrative built on the media regarding implementing the Presidential Threshold is more dominated by the contrast. This is inseparable from the political interest ahead of the 2024 general election. Namely, to carry and win presidential and vice-presidential candidates who are supported by each political actor involved.